Sukuk (Obligasi Syariah) dalam Perspektif Keuangan Islam - Maula Nasrifah (Asy-Syari’ah : Jurnal Hukum Islam, 2019)
Islam strongly encourages investment so that possessions can be productive and bring benefits in the future, of course, using a good and right way, which is in accordance with Islamic sharia, like mutual respect and does not harm others. The type of investment can be varied, we can invest through the capital market, one of which is sukuk. Sukuk are securities that are proof of ownership (claim) on assets, whether in the form of tangible, intangible or project contracts from certain activities that require the issuer to pay revenue-sharing to the Sukuk holders and pay back the Sukuk in maturity date. The principle in Sukuk transactions is in the form of emphasis on fair agreements, recommendations for profit sharing systems. In Sukuk transaction, a number of certain assets are needed which to used as the basis for conducting transactions using a contract based on sharia principles. The types of Sukuk in terms of Sukuk Ijarah, Sukuk Mudharabah, Sukuk Musyarakah, Sukuk Istishna’ with the method of issuing in bookbuilding, auction methods and private placement. In sukuk transactions there is a requirement for Underlying Assets as well as activities or processes which have been based in accordance with sharia. This shows that investing with sukuk is not worrying for investors who want to transact with sharia financial institutions. Keywords: Investing, Transaction, Sukuk